"I'm supposed to feel like this is my home": Testing terms of sociopolitical inclusion in an inner-ring suburban high school. Issue 5 (18th June 2018) - Shirazi, Roozbeh
Abstract : Purpose: The purpose of this paper is to examine how the exercise of administrative authority to suspend the Muslim Student Association (MSA), an affinity group at a suburban Midwestern high school, was experienced and perceived by affected students. Notably, it traces the mobilization of the MSA students to challenge the principal's authority through formal channels within the district to reopen the affinity group. In doing so, the students' activism represents an example of dissensus, or mode of political engagement that challenges top-down models of fostering equity and diversity in schools. Design/methodology/approach: The data are drawn from a nine-month ethnographic case study at an inner-ring suburban school in a large Midwestern metropolitan area. Data include participant observation of classrooms and affinity group meetings, semi-structured individual and group interviews, informal conversation and analytical memos synthesizing ethnographic fieldnotes. Findings: Though the school and district have made different investments in strengthening equity and diversity at the school, transnational and minoritized Muslim students report a school climate that is characterized by exclusion and racialized surveillance. The principal's decision to suspend the MSA was characterized by a narrow understanding of the purpose of the group and the identities of the student members. The decision to suspend the MSA, however, produced conditions centering the agentive potential of marginalized and minoritized students. Originality/value: This paper opens up the tensions challenges of incorporating student voice into educational decision making. Notably, it highlights important possibilities for political action students when their voices cannot or will not be heard by those who make decisions on their behalf.